2021
DOI: 10.1108/rbf-02-2021-0021
|View full text |Cite
|
Sign up to set email alerts
|

Herding in the crypto market: a diagnosis of heavy distribution tails

Abstract: PurposeWith the unprecedented growth of digitalization across the globe, a new asset class, that is cryptocurrency, has emerged to attract investors of all stripe. The novelty of this newly emerged asset class has led researchers to gauge anomalous trade patterns and behavioural fallacies in the crypto market. Therefore, the present study aims to examine the herd behaviour in a newly evolved cryptocurrency market during normal, skewed, Bitcoin bubble and COVID-19 phases. It, then, investigates the significance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 88 publications
5
18
0
Order By: Relevance
“…Mandaci and Cagli (2022), employing a novel Granger causality methodology with a Fourier approximation, find significant herding behaviour during the COVID-19 outbreak, whilst Lee et al. (2021) and Shrotryia and Kalra (2021), find that herding effect is present, only during down markets in periods of high volatility and up markets in periods of low volatility, and during normal, bullish and high volatility periods accordingly. Finally, in their study, Rubbaniy et al.…”
Section: Herding In Cryptocurrenciesmentioning
confidence: 98%
See 2 more Smart Citations
“…Mandaci and Cagli (2022), employing a novel Granger causality methodology with a Fourier approximation, find significant herding behaviour during the COVID-19 outbreak, whilst Lee et al. (2021) and Shrotryia and Kalra (2021), find that herding effect is present, only during down markets in periods of high volatility and up markets in periods of low volatility, and during normal, bullish and high volatility periods accordingly. Finally, in their study, Rubbaniy et al.…”
Section: Herding In Cryptocurrenciesmentioning
confidence: 98%
“…On the other hand, the analysis of Susana et al (2020) revealed that herding was present amongst all cryptocurrencies of the sample in normal conditions, but not during market upswing or downswing. Mandaci and Cagli (2022), employing a novel Granger causality methodology with a Fourier approximation, find significant herding behaviour during the COVID-19 outbreak, whilst Lee et al (2021) and Shrotryia and Kalra (2021), find that herding effect is present, only during down markets in periods of high volatility and up markets in periods of low volatility, and during normal, bullish and high volatility periods accordingly. Finally, in their study, Rubbaniy et al (2020), utilise over 100 cryptocurrencies in order to investigate the phenomenon.…”
Section: Herding In Cryptocurrencies During the Pandemicmentioning
confidence: 98%
See 1 more Smart Citation
“…In the same way, Montasser et al (2022) have examined the efficiency of 18 cryptocurrency markets and showed that the COVID-19 pandemic significantly affects their behavior. Several studies have explained this fact through behavioral biases (Shrotryia and Kalra, 2021;Mnif and Jarboui, 2021;Shrotryia and Kalra, 2021). Most studies consider that cryptocurrency prices are fundamentally bubbles, as they have neither an intrinsic value nor provide dividends (Geuder et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…CSADs have been a popular measure of herding intensity within the cryptocurrency markets. Rubbaniy et al, 2021 , Shrotryia and Kalra, 2021 employ it on daily datasets of 101 and 83 cryptocurrencies respectively, from 2015 to 2020, and reveal the presence of herding during bullish and high-volatility periods. Using CSADs and GARCH on six cryptocurrencies from January 2015 to March 2019, Ballis & Drakos (2020) conclude that herding is present during both up- and down-market days.…”
Section: Introductionmentioning
confidence: 99%